Challenges of Endoscopic Management of Pancreaticobiliary Complications in Surgically Altered Gastrointestinal Anatomy - Wai, Tin Moe (Clin Endosc, 2016)
Pancreaticobiliary complications following various surgical procedures, including liver transplantation, are not uncommon and are important causes of morbidity and mortality. Therapeutic endoscopy plays a substantial role in these patients and can help to avoid the need for reoperation. However, the endoscopic approach in patients with surgically altered gastrointestinal (GI) anatomy is technically challenging because of the difficulty in entering the enteral limb to reach the target orifice to manage pancreaticobiliary complications. Additional procedural complexity is due to the need of special devices and accessories to obtain successful cannulation and absence of an elevator in forward-viewing endoscopes, which is frequently used in this situation. Once bilioenteric anastomosis is reached, the technical success rates achieved in expert hands approach those of patients with intact GI anatomy. The success of endoscopic therapy in patients with surgically altered GI anatomy depends on multiple factors, including the expertise of the endoscopist, understanding of postoperative anatomic changes, and the availability of suitable scopes and accessories for endoscopic management. In this issue of Clinical Endoscopy, the focused review series deals with pancreatobiliary endoscopy in altered GI anatomy such as bilioenteric anastomosis and post-gastrectomy.